Faktor-Faktor Penyebab Rendahnya Prestasi Belajar Di Sekolah Menengah Atas Katolik Swasta Syuradikara Ende - Ludgardis Bete Kiik Huwa; Stefanus Hubertus Gusti Ma (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
This study aims to determine the factors causing low learning achievements of students majoring in social studies class XI on economic subjects at a private Catholic High School Syuradikara Ende. This study uses quantitative methods. Data collection techniques used in this research is by using questionnaires, and documentation. Analysis of the data used in this study were the validity, reliability, and ending with the model of factor analysis. From the results of data analysis has been done, the data showed that there are 28 factors that lead to low learning achievement of students majoring in social studies class XI on economic subjects in the Catholic High School Private Syuradikara Ende. All 28 factors are grouped into four component factors that lead to low achievement of learners that is the name of the component combined 1 (internal and external factors) with a percentage of 50,206%, the components of the combined 2 (internal and external factors) with a percentage 15,758%, 3 combined components (internal and external factors) with a percentage of 10,455%, and the last component 4 (external factors) with a percentage of 7,937%.